Preventing soil degradation in shifting cultivation using integrated farming system models. Issue 13 (10th November 2022) - Chatterjee, Dibyendu; Kuotsu, Rukuosietuo; Ray, Sanjay Kumar; Patra, M. K.; Thirugnanavel, A.; Kumar, Rakesh; Borah, T. R.; Chowdhury, Pulakabha; Pongen, Imliakum; Satapathy, B.S.; Deka, Bidyut C.
ABSTRACT: Integrated farming system (IFS) based shifting cultivation reduces soil erosion and outperform in terms of productivity and income generation in North-Eastern Hills of India. To address this hypothesis, an experiment was conducted at Jharnapani, Nagaland, India with five treatments, viz., natural vegetation (NV), animal-based IFS (IFA), horticulture-based IFS (IFH), traditional shifting cultivation (TS) and traditional shifting cultivation with minor interventions (TSM). The soil moisture (34%), available N (23%), soil organic carbon (35%), bacterial (56%) and fungal (54%) counts decreased after burning of natural vegetation. Burning increased soil pH (10%), EC (131%), available P (62%), and available K (53%) for a short period. Improved integrated farming system models such as IFA and IFH were found to reduce soil erosion (34–48%) and loss of SOM (26–51%), N (33–45%), P (19–54%) and K (27–51%) compared to the traditional system (TS). Moreover, the improved models like IFA and IFH had a higher net return (0.07–52% higher) compared to TS. Considering all these facts, IFA/IFH can be recommended for the North Eastern Hill region based on suitability of altitude, socio-economic status of the farmers, farmers' preference and demand in the local market.